The Influence of Islamic Product Quality and Design on Muslim Consumer Interest in Arung Meubel Products in Sorong City - Rokhimah Rokhimah; Andi Hasrun; Bambang Sunatar; Karfin Karfin; Susetyowati Sofia (Universitas Nurul Jadid, 2023)
This study aims to determine how much impact or influence arises from product quality and Islamic design on Muslim consumer satisfaction on Arung Meubel sofa products in the city of Sorong. To achieve this goal, the research method used is quantitative. The data in this study were obtained through a questionnaire with respondents (consumers of Arung Furniture). The number of samples used in this study were 30 respondents. Data analysis techniques in this study used multiple linear regression, f test, coefficient of determination (simultaneous), and t - test (partial). The results of the study show that product quality and Islamic design have a significant effect on Muslim consumer satisfaction. Based on the results of the validity test, reliability test and hypothesis testing, namely the simultaneous test (f - test), the coefficient of determination, and the partial test (t - test) product quality (X1) and design (X2) showed that the results of these tests show a significant effect on consumer satisfaction (Y).